2023
DOI: 10.3390/nu15071703
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study on Zinc-Related Metabolism in Breast Cancer

Abstract: Breast cancer has become the most common cancer worldwide. Despite the major advances made in the past few decades in the treatment of breast cancer using a combination of chemotherapy, endocrine therapy, and immunotherapy, the genesis, treatment, recurrence, and metastasis of this disease continue to pose significant difficulties. New treatment approaches are therefore urgently required. Zinc is an important trace element that is involved in regulating various enzymatic, metabolic, and cellular processes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 138 publications
0
6
0
Order By: Relevance
“…Zn is an important trace element in the body and is involved in regulating numerous cellular metabolic processes. Abnormal Zn metabolism can lead to the development and progression of BC ( 11 ). However, studies on the prognostic value of genes related to Zn metabolism in BC have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Zn is an important trace element in the body and is involved in regulating numerous cellular metabolic processes. Abnormal Zn metabolism can lead to the development and progression of BC ( 11 ). However, studies on the prognostic value of genes related to Zn metabolism in BC have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it has been observed that a high expression of ZIP6 is considered a trustworthy indicator of luminal A subtypes in breast cancer. Moreover, ZIP6 expression is a predictor of tumor stage and grade and has a major impact on the biological activity of breast cancer cells [187][188][189][190]. Furthermore, cancer progression and metastasis can be accelerated by the impairment of MMPs, especially MMP2 and MMP9, which are a subgroup of Zn-dependent MMPs.…”
Section: Zincmentioning
confidence: 99%
“…Furthermore, cancer progression and metastasis can be accelerated by the impairment of MMPs, especially MMP2 and MMP9, which are a subgroup of Zn-dependent MMPs. Several studies reported EMT stimulation and the accelerated expansion of tumors due to increased MMP activity [188,191]. Holanda et al reported the direct as well as indirect role of MMPs in tumor growth.…”
Section: Zincmentioning
confidence: 99%
“…Additionally, Zn could be responsible for this enhancement in viability. A review of the literature conducted by Qu et al revealed that Zn levels in breast cancer tissues are significantly higher than in healthy tissue [73]. Moreover, a study by Rusch and colleagues demonstrated that breast cancer subtypes similar to that of the HCC2218 cell line (Her2 positive breast cancer) absorbed levels of Zn ranging from 7-10 ppm [74].…”
Section: Chemotherapeutic Potential and Cytotoxicitymentioning
confidence: 99%